Lymphadenopathy: Defining a palpable lymph node. Issue 2 (11th February 2014) - Xu, Jason J.; Campbell, Gordon; Alsaffar, Hussain; Brandt, Michael G.; Doyle, Philip C.; Glicksman, Jordan T.; Fung, Kevin
Abstract Background The threshold size required to detect lymphadenopathy via palpation has never been formally determined. The purpose of this study was to determine the threshold, sensitivity, and error of node palpation and how this changes with experience. Methods Lymphadenopathy models were created using polyvinyl alcohol cryogel (PVA‐C) to mimic tissue tactility. Node diameter ranged from 0.5 to 4 cm. Study subjects were medical students, otolaryngology residents, and otolaryngology consultants. Each subject provided 22 estimates of size. Primary outcomes were the sensitivity, error (true vs estimated size), and threshold of palpation. Results Thirty subjects completed the study. Sensitivity was 60%, 74%, and 86% for students, residents, and consultants, respectively (p < .01). Error was 0.88 cm, 0.61 cm, and 0.57 cm, respectively (p < .05). Palpation threshold was 1.32 cm, 0.83 cm, and 0.75 cm, respectively (p < .05). All participants detected nodes ≥2 cm, whereas consultants detected nodes ≥1 cm. Conclusion Experience is associated with decreased palpation threshold and error, and increased sensitivity. Educational interventions should target nodes <2 cm. © 2014 Wiley Periodicals, Inc. Head Neck37: 177‐181, 2015